The lived experiences of women principals in rural secondary schools regarding their career pathways - Mthethwa, Joyce F.; Kutame, Azwidohwi P.; Buthelezi, Alan B.; Ajani, Oluwatoyin Ayodele (Penerbit Universiti Kebangsaan Malaysia, 2022)
This interpretivist qualitative study explored lived experiences of rural secondary schools’ female principals' career development. Purposive sampling technique was employed to select eleven female principals from 11 rural public secondary schools in Ilembe District, KwaZulu-Natal, South Africa to provide in depth information to the study. A semi-structured interview guide was used in various audio-recorded interviews, which lasted between 20-30 minutes each to capture exact information. The audio-recorded data was systematically transcribed and coded to generate common themes for the presentation and discussion of findings. Findings revealed that some communities’ cultures continue to dominantly influence women principals’ career pathways, despite policies or efforts to promote gender equality in South Africa. The social attitude or ‘injustice’ against female principals in rural environments has limited their quest to pursue their careers further or to aspire to top administrative leadership positions in education. It is recommended that necessary government structures and other stakeholders in the education sector should provide the necessary support to encourage female principals in rural schools.